2012
DOI: 10.1140/epje/i2012-12001-6
|View full text |Cite
|
Sign up to set email alerts
|

Particle-like and fluid-like settling of a stratified suspension

Abstract: Abstract. The gravitational settling of inhomogeneously suspended particles in fluid has been investigated. Of particular interest is whether collective or individual motion of particles is dominant during their settlings, i.e., whether the particles settle as a continuous suspension or they settle individually relative to surrounding fluid. We observed the settling of a stratified suspension which has the lower and upper concentration interfaces in quasi-two dimensional vessel. In some cases, the suspension b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(44 citation statements)
references
References 24 publications
4
40
0
Order By: Relevance
“…As can be seen, finger-like instability develops at concentration interface and the settling of suspended particle is subject to macroscopic motion of the interface instabilities. As described in our previous article (Harada et al, 2012), such fingering instability is fundamentally the same as Rayleigh-Taylor instability and it behaves as immiscible fluids if the particle size is small and the concentration is high,…”
Section: Settling Behavior Of Suspensionmentioning
confidence: 75%
See 3 more Smart Citations
“…As can be seen, finger-like instability develops at concentration interface and the settling of suspended particle is subject to macroscopic motion of the interface instabilities. As described in our previous article (Harada et al, 2012), such fingering instability is fundamentally the same as Rayleigh-Taylor instability and it behaves as immiscible fluids if the particle size is small and the concentration is high,…”
Section: Settling Behavior Of Suspensionmentioning
confidence: 75%
“…Before that, we reconsider the experimental results of the gravitational settling of various-sized particles described in our previous article (Harada et al, 2012). Fig.9 is the settling velocity of particles in quasi-two dimensional closed channels.…”
Section: Prediction Of Settling Velocity In Arbitrary Channelmentioning
confidence: 95%
See 2 more Smart Citations
“…For the second case in which the concentration interface points down, Harada et al (2012) have experimentally examined the collectivity of settling particles caused by the Rayleigh-Taylor instability. They found that the transition from individual to collective settling of suspended particles is determined by a dimensionless parameter given by the ratio of the interparticle separation to the dominant wavelength of the instability; this ratio is related to the number density of the suspended particles.…”
Section: Introductionmentioning
confidence: 99%